Advances on Coastal and Estuarine Circulations Around the Changjiang Estuary in the Recent Decades (2000–2020) - Liu, Zhiqiang; Gan, Jianping; Wu, Hui; Hu, Jianyu; Cai, Zhongya; Deng, Yongfei (Frontiers in Marine Science, 2021)
Advances on the circulation in the Changjiang Estuary and adjacent East China Sea (ECS) and Yellow Sea (YS) coastal waters in the recent decades (2000-2020) are synthesized in this review. The circulation over the complicated bathymetry in the region is locally driven by winds, tides, as well as riverine discharge, and is remotely influenced by shelf currents between the 50-m and 100-m isobaths through the cross-shelf exchanges. The interchange of the momentum and the freshwater pathway inside the Changjiang Estuary are jointly determined by tides and seasonally varying discharge and winds over the shelf. The buoyant waters are trapped inside the bulge that forms and expands over the shelf to the west of the 30-m isobath in the vicinity of Hangzhou Bay and the Changjiang Estuary. These buoyant waters are exported offshore by the shelf current, tidal mixing, and variations of wind patterns, forming the Changjiang River plume, which shows notable seasonality due to the reversal of both winds and shelf currents in the ECS and YS. Extensive spatial irregularities in the form of freshwater patches is present along its pathway to the Tsushima Strait in summer and to the Taiwan Strait in winter, respectively. Tides and the bathymetry irregularity have recently been found to play critical roles in determining the cross-shelf exchanges of water mass and momentum along the pathway of the ECS coastal current, and along this pathway, a year-round upslope intrusion of shelf waters appears in both summer and winter. Tides also play an important role in altering the expansion of the Changjiang River plume, cross-shelf extrusion of waters, and variation in the Yellow Sea Coastal Current over the shallow Subei Shoal.